Cover Feature: Photoresponsive Binding Dynamics in High‐Affinity Cucurbit[8]uril‐Dithienylethene Host‐Guest Complexes (Chem. Eur. J. 37/2021) - Colaço, Miriam (2022)
Photoresponsive binding kinetics was achieved in cucurbit[8]uril-dithienylethene host-guest complexes. This work demonstrates that, in the presence of a competitor guest (in purple), the host-guest dissociation kinetics is approximately 100-fold slower for the closed (green) than for the open (yellow) dithienylethene isomers (t 1/2=107 hours vs. t 1/2=1.2 hours), allowing control over the dissociation rate with red/NIR light. More information can be found in the Full Paper by A. Jorge Parola, N. Basílio, et al. (DOI: 10.1002/chem.202100974).